SNX27:Retromer:ESCPE-1-mediated early endosomal tubulation impacts cytomegalovirus replication - Štimac, Igor; Marcelić, Marina; Radić, Barbara; Viduka, Ivona; Blagojević Zagorac, Gordana; Lukanović Jurić, Silvija; Rožmanić, Carmen; Messerle, Martin; Brizić, Ilija; Lučin, Pero; Mahmutefendić Lučin, Hana (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionCytomegaloviruses (CMVs) extensively reorganize the membrane system of the cell and establish a new structure as large as the cell nucleus called the assembly compartment (AC). Our previous studies on murine CMV (MCMV)-infected fibroblasts indicated that the inner part of the AC contains rearranged early endosomes, recycling endosomes, endosomal recycling compartments and trans-Golgi membrane structures that are extensively tubulated, including the expansion and retention of tubular Rab10 elements. An essential process that initiates Rab10-associated tubulation is cargo sorting and retrieval mediated by SNX27, Retromer, and ESCPE-1 (endosomal SNX-BAR sorting complex for promoting exit 1) complexes.ObjectiveThe aim of this study was to investigate the role of SNX27:Retromer:ESCPE-1 complexes in the biogenesis of pre-AC in MCMV-infected cells and subsequently their role in secondary envelopment and release of infectious virions.ResultsHere we show that SNX27:Retromer:ESCPE1-mediated tubulation is essential for the establishment of a Rab10-decorated subset of membranes within the pre-AC, a function that requires an intact F3 subdomain of the SNX27 FERM domain. Suppression of SNX27-mediated functions resulted in an almost tenfold decrease in the release of infectious virions. However, these effects cannot be directly linked to the contribution of SNX27:Retromer:ESCPE-1-dependent tubulation to the secondary envelopment, as suppression of these components, including the F3-FERM domain, led to a decrease in MCMV protein expression and inhibited the progression of the replication cycle.ConclusionThis study demonstrates a novel and important function of membrane tubulation within the pre-AC associated with the control of viral protein expression.